Respostas
respondido por:
2
6x - 4 = 2x + 8 Separe os termos, troque os sinais
6x - 2x = 8 + 4 Efetue as operações
4x = 12 Divida ambos os lados por 4
x = 3
6x - 2x = 8 + 4 Efetue as operações
4x = 12 Divida ambos os lados por 4
x = 3
maxwele:
muito obrigada ;)
respondido por:
3
6x - 4 = 2x + 8
6x - 2x = 8 + 4
4x = 12
x = 12/4
x= 3
6x - 2x = 8 + 4
4x = 12
x = 12/4
x= 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás